MULTIDRUG-RESISTANT AND EXTENSIVELY DRUG-RESISTANT TUBERCULOSIS IN INDONESIA: A CRITICAL REVIEW OF TRENDS, DETERMINANTS AND CONTROL STRATEGIES - Azkiyah, Siti Zamilatul (PARADIGM : Journal Of Multidisciplinary Research and Innovation, 2025)
Multidrug-resistant tuberculosis (MDR-TB) and extensively drug-resistant tuberculosis (XDR-TB) pose major challenges to tuberculosis control in Indonesia, a country with one of the highest TB burdens globally. This review critically examines trends, determinants, and control strategies of MDR/XDR-TB in Indonesia. A narrative critical review was conducted using national and international literature published over the last 10–15 years, focusing on epidemiology, risk factors, diagnostic approaches, and treatment outcomes. The findings indicate that previous TB treatment, poor treatment adherence, and comorbidities such as diabetes mellitus are key determinants of drug resistance. Although molecular diagnostic tools have improved early detection, unequal access and health system limitations persist. New therapeutic regimens offer improved outcomes but remain constrained by adherence issues and emerging resistance. An integrated, evidence-based approach addressing clinical, social, and system-level factors is essential to strengthen MDR/XDR-TB control in Indonesia.